Screen-based activities and physical complaints among adolescents from the Nordic countries - Bjarnason Thoroddur; Hansen Fredrik; Schnohr Christina W; Eriksson Lilly; Torsheim Torbjørn; Välimaa Raili (BMC, 2010)
Abstract Background A positive association between time spent on sedentary screen-based activities and physical complaints has been reported, but the cumulative association between different types of screen-based activities and physical complaints has not been examined thoroughly. Methods The cross-sectional association between screen-based activity and physical complaints (backache and headache) among students was examined in a sample of 31022 adolescents from Denmark, Sweden, Norway, Finland, Iceland and Greenland, as part of the Health behaviour in school-aged children 2005/06 (HBSC) study. Daily hours spent on screen-based activities and levels of physical complaints were assessed using self-reports. Results Logistic regression analysis indicated that computer use, computer gaming and TV viewing contributed uniquely to prediction of weekly backache and headache. The magnitude of associations was consistent across types of screen based activities, and across gender. Conclusion The observed associations indicate that time spent on screen-based activity is a contributing factor to physical complaints among young people, and that effects accumulate across different types of screen-based activities.